Analisis Performa Operating System Android Pada Implementasi Aplikasi Media Belajar Bahasa Isyarat IConnect - Lintang Firdaus (Universitas Pendidikan Muhammadiyah Sorong, 2024)
This study evaluates the impact of the Android 12 operating system on the IConnect application in the context of sign language learning (BISINDO). The focus is on managing CPU, memory, and storage while applications are running. Artificial state observation uses an experimental approach to understanding the influence of the variables manipulated. Observations show variations in CPU usage, memory, and storage requirements during application operation. It is important to optimize CPU performance, efficient memory management, and the right storage strategy to scale applications. The results show that the IConnect application can be enhanced to provide a more effective learning experience for BISINDO users. In short, improved application performance will bring better benefits to Sign Language Indonesia users.